Effect Of Dosage And Frequency Of Liquid NPK Fertilization On Growth Of Cutting Seedlings Robusta Coffee (Coffea chanephora) - Muhammad Yordan Yuliano Al amin; Gatot Subroto; Distiana Wulanjari; Dyah Ayu Savitri (Protech Biosystems Journal, 2023)
The Robusta coffee plant (Coffea canephora) is included in the Rubiaceae family and the Coffea genus. The problem in breeding Robusta coffee plants is that Robusta coffee seeds cannot be developed generatively because of the type of cross-pollination, so they must be propagated vegetatively by cuttings, namely slow root growth and rooting. weak so shoot formation is slow. To overcome this problem, liquid NPK fertilizer (24:20:05) was used with the aim of producing optimal cutting growth. The aim of this research was to determine the effect of the dose and frequency of application of liquid NPK fertilizer (24:20:05) on the growth of Robusta coffee cuttings. The method used was a factorial Randomized Block Design (RAK) consisting of 2 factors and 3 replications. Factor 1 consists of F0: 0 ml/polybag, F1 (25 ml/polybag), F2 (50 ml/polybag), F3 (75 ml/polybag), F4 (100 ml/polybag). The second factor is the frequency of fertilization (M) which consists of M1: Application once a week M2: Application once every 2 weeks M3: Application once every 3 weeks. The research results showed that there was an interaction between the dose of liquid NPK fertilizer and the frequency of fertilization on Robusta coffee cuttings (1) which had a very significant influence on the observed variables of stem diameter, number of branches and leaf area. (2) Giving a dose of liquid NPK fertilizer to Robusta coffee plant cuttings has a very real influence on all variables. (3) The effect of fertilization frequency on Robusta coffee plant cuttings has a very real influence on the variables of stem diameter and number of branches.